A comprehensive comparison of hematological parameters among 39 common diseases. (19th May 2019) - Gao, Xing; Yin, Junping; Wang, Xiaoli; Petersen, Frank; Yu, Xinhua
Abstract: Hematological parameters have been shown to be associated with morbidity and/or mortality of various disorders such as inflammatory diseases and cancer. In this study, we performed a comprehensive comparison of hematological parameters among 39 diseases, including cancer, inflammatory, autoimmune, allergic and infectious diseases as well as some further common disorders. In total, 19, 038 patients and 23, 610 matched healthy controls were recruited and evaluated. Our results revealed distinct hematological profiles among disease groups in which erythrocyte-related parameters were specifically associated with cancer, neutrophil- and lymphocyte-related parameters were associated with inflammatory diseases, viral infectious diseases, cancer, autoimmune and allergic diseases and platelets-related parameters were associated with viral infectious diseases. Furthermore, both neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios were significantly higher in patients with inflammatory diseases, cancer, autoimmune and allergic diseases than corresponding controls. In addition, receiver operating characteristic curve analysis showed that several hematological parameters showed good diagnostic values for cancer, inflammatory diseases, and viral infectious diseases. Therefore, our results provide a valuable resource of hematological abnormalities in common diseases.